ANALISIS YURIDIS PELAKSANAAN JUAL BELI SECARA ONLINE PADA OVERDOSIS CLOTHES GALLERY DAN WINNI BOUTIQUE DI KOTA MEDAN - Muhammad Yasid (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2019)
Today's economic development raises new ways for people to conduct buying and selling transactions, namely by using informatics technology which is often referred to as online. The means used in this transaction are computers, and most recently through mobile phones. Online buying and selling can be found in various buying and selling forums, such as OLX.com, Bukalapak.com, the Kaskus buying and selling forum and the Medan Overdose Chlotes Gallery, Winni Boutique. Besides that, there are also individual businesses that do business buying and selling online. The process of implementing online buying and selling agreements in Overdose Clothes Gallery and Winni Boutique is carried out in four stages, namely offering, receiving, paying and shipping goods, but there are also payments made at the final stage. The factor of default in online buying and selling transactions is internal factors and external factors. The settlement taken in resolving defaults never reaches the legal route, but by deliberation and giving discounts and repairing clothes that have a disability to buyers who suffer losses